Antibacterial microcins are ubiquitous and functionally diverse across bacterial communities - Jennifer K. Parker; Aaron L. Feller; Richard Gu; Simon Sanchez-Paiva; Bethany C. Perez; Angela C. O’Donnell; Wendi Deng; Rita M. Ousterhout; Sun-Young Kim; Claus O. Wilke; Bryan W. Davies (Nature Communications)
Abstract Bacteria produce antibacterials that drive competition and regulate community composition. While diverse examples have been found, few families of antibacterial agents appear to be widespread across phylogenetically divergent bacteria. Here, we show that what appeared to be a limited, niche class of Gram-negative bacteriocins, called class II microcins, is in fact a highly abundant, sequence- and function-diverse class of secreted bacteriocins. Based on systematic investigations in the Enterobacteriaceae and gut microbiomes, we demonstrate that class II microcins encompass diverse sequence space, bacterial strains of origin, spectra of activity, and mechanisms of action. Importantly, we show microcins discovered here are active against pathogenic E. coli during mouse gut colonization, supporting important roles for these unrecognized antibacterials in vivo. Our study reveals the overlooked abundance and diversity of microcins found dispersed throughout Bacteria and opens opportunities to uncover and exploit mechanisms of competition to modulate microbial communities.